2021
DOI: 10.1111/all.15139
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of epidemiologic surveillance and Google Trends data on asthma and allergic rhinitis in England

Abstract: To the Editor, Epidemiologic surveillance is the 'ongoing systematic collection, analysis, and implementation of health data essential to the planning, implementation and evaluation of public health practices, closely integrated with the timely dissemination of these data'. 1 Recently, the use of data from internet users' activity-measured with tools such as Google Trends (GTs)-has been proposed to complement 'classical' surveillance approaches. 2 In this context, infectious diseases have been widely studied, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Combined with pollen concentration data, web search data may therefore support monitoring and prediction of asthma incidence and hospitalizations, as has been proposed and attempted previously. 14 , 22 Further studies are needed to verify this approach. Moreover, climate change is already affecting pollen load, leading to higher or lower prevalence, intensity, and duration of sensitization depending on the type of pollen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Combined with pollen concentration data, web search data may therefore support monitoring and prediction of asthma incidence and hospitalizations, as has been proposed and attempted previously. 14 , 22 Further studies are needed to verify this approach. Moreover, climate change is already affecting pollen load, leading to higher or lower prevalence, intensity, and duration of sensitization depending on the type of pollen.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has examined online search queries for asthma, mainly focusing on allergic rhinitis and pollen season 18 , 19 , 20 and using the relative number of searches. 14 , 21 , 22 Studies comparing the absolute number of searches for different asthma search terms in European countries to investigate possible unmet needs in the European population are still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Google Trends data have been used to monitor both chronic and acute diseases. Search volume data related to the common cold were found to be correlated with asthma incidence and to forecast asthma hospitalizations [ 8 , 9 ]. Additionally, Fang and colleagues [ 10 ] found that an increase in searches related to chronic obstructive pulmonary disease from 2007 to 2020 was correlated with several estimates of chronic obstructive pulmonary disease morbidity.…”
Section: Introductionmentioning
confidence: 99%